Inappropriate emergency laboratory test ordering: defensive or peer evidence shared based medicine? - C. Descovich; R. Nardi; A. Ligabue; G. Gaspari; E. Dini; G. Pieroni; M. Annichiarico (Italian Journal of Medicine, 2013)
BACKGROUND The laboratory overuse is widely prevalent in hospital practice, mostly in the emergency care. Reasons for excessive and inappropriate test-ordering include defensive behaviour and fear or uncertainty, lack of experience, the misuse of protocols and guidelines, “routine” and local attitudes, inadequate educational feedback and clinician’s unawareness about the cost of examinations and their related implications. AIM OF THE STUDY AND METHODS The primary target of our working group was to reduce inappropriate ordering on a urgent basis test, implementing further examinations not yet previewed in the hospital panel of the available urgencies, according to the evidence based diagnosis concept. The secondary goal was to indicate strategies of re-engineering of the processes, improving turnaround time in the laboratory management of emergencies. After evaluating, as first intervention, the more reliable sources for practice guidelines, systematic reviews and RCTs, the committee further discussed main topics with in-hospital stakeholders, selected from Emergency, Internal Medicine and Surgery Depts. The working group, in many subsequent audits, tried to obtain a systematic feed back with all involved professionals. RESULTS After reviewing literature’s evidence, the board constrained testing options by defining the basic emergency laboratory panel tests (blood type, hemogram, blood urea nitrogen, plasma creatinine, glucose, sodium, potassium, chloride, osmolarity, CRP, bicarbonate, CPK, creatine phosphokinase-MB, myoglobin, troponin, BNP and NT-proBNP, PT-INR, PTT, D-dimer, beta- HCG, biochemical urinalysis etc.). As final result, the proposed tests reduced the overall number of inappropriate investigations and increased, with newer and updated tests, the available panel for critical patients. DISCUSSION A collegiate review of data reporting, in-hospital deepening of problems and the inter- professional discussion of the evidences, defining the “best – locally applicable – standard of care”, are suitable tools to facilitate communication for reducing inappropriate test-ordering. CONCLUSIONS Excessive ordering increases the use of technology and adds unnecessary costs to the delivery of health care. Hospitals with growing health care costs can improve their resource utilization through peer management of testing behaviours by using evidence based medicine for clinical audit. A basic, homogeneous and shared panel of critical tests may be adopted even in complex health organizations, including several hospitals too.